2003
DOI: 10.1103/physrevb.68.220401
|View full text |Cite
|
Sign up to set email alerts
|

Vectorial mapping of exchange anisotropy in IrMn/FeCo multilayers using the reversible susceptibility tensor

Abstract: A method for probing exchange anisotropy based on reversible susceptibility tensor is proposed. The experimental results obtained on exchange biased IrMn/FeCo multilayers are supported by the theoretical analysis of the transverse and longitudinal susceptibilities in the case of exchange-coupled systems. The vectorial mapping of the exchange bias in the studied sample is performed by detecting a composite signal containing both transverse and longitudinal susceptibilities for different orientations of the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…We have successfully applied this technique to several materials in thin-film form such as epitaxially grown CrO 2 thin films [12]. TS has also been used to study exchange biased IrMn/FeCo multilayers [13], fine-particle systems such as BaFe 12 O 19 [14], g-Fe 2 O 3 nanoparticles [15], Au-Fe core-shell nanoparticles [16] and magnetic recording media [17]. In a recent study, we had reported systematic TS measurements to resolve the nature of in-plane and out-of-plane dipolar interactions in multilayered nanoparticle arrays of Fe [18].…”
Section: Introductionmentioning
confidence: 98%
“…We have successfully applied this technique to several materials in thin-film form such as epitaxially grown CrO 2 thin films [12]. TS has also been used to study exchange biased IrMn/FeCo multilayers [13], fine-particle systems such as BaFe 12 O 19 [14], g-Fe 2 O 3 nanoparticles [15], Au-Fe core-shell nanoparticles [16] and magnetic recording media [17]. In a recent study, we had reported systematic TS measurements to resolve the nature of in-plane and out-of-plane dipolar interactions in multilayered nanoparticle arrays of Fe [18].…”
Section: Introductionmentioning
confidence: 98%
“…Transverse susceptibility ͑TS͒ is one of the most sensitive methods in determining the magnetic anisotropy, and it was used with great success to characterize close-packed arrays of monodisperse Fe nanoparticles, 1 Fe͑001͒ square nanostructures, 2 exchange-biased IrMn/ FeCo multilayers, 3 epitaxial CrO 2 and CrO 2 /Cr 2 O 3 bilayer thin films, 4,5 and perpendicular recording media. Also, there is a great interest in describing theoretically the transverse susceptibility in magnetic nanosized systems.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some of the restrictions in the first theoretical approach of Aharoni et al 8 were overcome [10][11][12][13][14][15] and the increased sensitivity of new experimental TS methods allowed the investigations of magnetic systems with very low concentration of magnetic moments. 3,4,16,17 A very recent development of TS constitutes the complex TS. It was first mentioned by Papusoi 18 in the context of magnetic particulate systems and it spurred a lot of attention as it was presented as a new way to determine the particle volume and anisotropy field distributions of a particulate medium.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The theoretical study of transverse susceptibility ͑TS͒ was not subject to substantial changes after Aharoni's classical-article 2 in which the first comprehensive theoretical description of the reversible susceptibility tensor for the Stoner-Wolfarth model 4 was given. Subsequent theoretical approaches of TS overcame some limitations of Aharoni's approach by taking into account magnetic systems with different types of anisotropy, [5][6][7] or studying the effect of interactions 8 and thermal relaxation. 8,9 What is common to all papers published previously and dealing with transverse susceptibility modeling is the theoretical approach used.…”
mentioning
confidence: 99%